(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of pregnant women with twin pregnancies ≥ 22 weeks diagnosed with preeclampsia at Can Tho Gynecology Obstetrics Hospital from 2024 to 2026. Subject and methods: A cross-sectional descriptive study was conducted on 44 pregnant women with twin pregnancies ≥ 22 weeks diagnosed with preeclampsia who were hospitalized for monitoring, treatment, and delivery at Can Tho Gynecology Obstetrics Hospital during the study period. Results: The mean maternal age was 30.7 ± 5.6 years, with 81.8% aged under 35 years. The mean pre-pregnancy BMI was 22.8 ± 3.3 kg/m²; 38.6% had a BMI ≥ 23 kg/m². Conception via assisted reproductive technologies accounted for 38.6%. The mean gestational age at onset of preeclampsia was 37.7 ± 3.1 weeks; 38.6% had onset before 34 weeks. Preeclampsia with severe features occurred in 52.3% of cases, and HELLP syndrome in 15.9%. The highest recorded systolic blood pressure averaged 155.5 ± 16.5 mmHg. Among those with severe features, 87% had severe hypertension; hemolysis was observed in 34.8%, thrombocytopenia and elevated liver enzymes each in 17.4%, and renal impairment in 13%. No factors were statistically significantly associated with severe preeclampsia; however, all cases with chronic hypertension were classified as having severe features (p = 0.050). Conclusion: Preeclampsia in twin pregnancies ≥ 22 weeks’ gestation was characterized by a high proportion of severe cases and a substantial rate of early-onset disease, accompanied by multiple manifestations of multi-organ involvement. Larger studies are warranted to further clarify predictors of severe disease.